Isolation of Bordetella trematum from the respiratory tract of a patient with lung cancer: a case report - Kukla, Rudolf; Svarc, Michal; Bolehovska, Radka; Ryskova, Lenka; Paterova, Pavla; Fajfr, Miroslav; Malisova, Lucia; Zemlickova, Helena (Folia microbiologica, 2020)
We report the case of isolation of Bordetella trematum from the respiratory tract of a patient with lung carcinoma. This gram-negative, opportunistic rod was firstly described in 1996. To date, only several strains of Bordetella trematum have been isolated and reported, mostly from skin and soft tissue infections. The patient was admitted to the ICU of the Pulmonary Department in incipient septic shock with respiratory failure. Intravenous fluid resuscitation and non-invasive ventilation were administered immediately. A broad spectrum antibiotic piperacillin/tazobactam was administered empirically after sampling of material for microbiological examination. The bronchoscopy showed a large cavern of decayed tumour invading into mediastinum. Both sample cultures showed significant quantities of gram-negative non-fermenting bacteria. The isolate was identified using MALDI-TOF MS as Bordetella trematum and the identification was confirmed using 16S ribosomal RNA sequencing. In the last few years, routine bacterial identification using MALDI-TOF MS has enabled correct discrimination of this species. Nevertheless, isolation of Bordetella trematum in clinical samples is still very uncommon, and it is appropriate to confirm the species identification via 16S ribosomal RNA sequencing. To our knowledge, this is the first case of B. trematum isolated from the human respiratory tract since its first description. The clinical significance of Bordetella trematum in the rapid deterioration of the patient's status remains unclear.
Keywords: Respiratory System; nádory plic; Respiratory tract; fatální výsledek; Lung Neoplasms; 16S rRNA sequencing; Humans; Bordetella; Aged; RNA ribozomální 16S; senioři; lidé; antibakteriální látky; RNA, Ribosomal, 16S; MALDI-TOF MS; Bordetella trematum; dýchací soustava; Bordetella Infections; Anti-Bacterial Agents; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Male; Fatal Outcome; infekce bakteriemi rodu Bordetella; mužské pohlaví; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Case report